Congenital Anomalies in Portugal: a Spatial and Temporal Characterization - Gomes, Dulce (2008)
The aim of this study is to understand spatial and temporal patterns of occurrences of these diseases, trying to identify explanatory variables or factors that could influence birth defects rates, according to the Portuguese registry of congenital anomalies. Specific statistical methods, such as spatial statistics and time series models, will be used to identify and characterize the mentioned patterns.